Extracurricular Physical Activities and the Condition of Being an Only Child as a Conditioning Factor in the Psychomotor Development of 5-Year-Old Children - Gil-Madrona, Pedro; Romero-Martínez, Sonia J.; Roz-Faraco, Carmen C. (Frontiers in Pediatrics, 2021)
In early childhood education, there is a great interdependence among motor, affective, and cognitive development. A better understanding of psychomotor development and its variables by pediatricians and those who oversee educational tasks at this stage of development, such as teachers, psychologists, counselors, and parents themselves, can influence the design of educational intervention proposals. To that effect, the present study aims to analyze the influence of some family characteristics such as the condition of being an only child or having siblings and whether the child carries out extracurricular activities linked to physical activities and sports. To achieve this objective, a Checklist of Psychomotor Activities (CPA) assessment instrument was used based on the observation of a sample of 694 children aged 5 years who were enrolled in the second cycle of child education in the province of Albacete. The results show that those children who performed extracurricular activities related to physical activities and sports had a greater development of laterality and postural tonic control than those who did not attend this type of activities. At the same time, differences were found in the affective and relational levels and in the perceptual-motor aspects in favor of children who have siblings compared with children who are only children. There is no other research that addresses both issues in the same study, and this is a strength of the present study.